2023
DOI: 10.34190/icgr.6.1.1199
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equity in Hospitals: An Italian case Study

Abstract: The topic of gender equity is increasingly cited as a goal of health policy despite the rise in the number of female doctors around the world, and attempts to enhance gender awareness have gained prominence. Recently, initiatives to increase gender awareness have been numerous nevertheless, the topic of gender equity in the medical profession has not been adequately assessed. In order to fill this gap, this paper examines the current state of gender equity literature in hospitals, with a systematic literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The "Gender Performance Initiative (GPI)" was initiated by "Women's World Banking" in 2011 to assess the efficacy of financial services firms in catering to women, both as customers and employees. Gravili et al (2019) examined GD across 28 European states and found a positive association between GD and FP. Zhang (2020) analyzed data from 2007 to 2014 and examined the impact of GD in the workforce.…”
Section: Gender Diversity (Gd) and Loan Size (Ls)mentioning
confidence: 99%
“…The "Gender Performance Initiative (GPI)" was initiated by "Women's World Banking" in 2011 to assess the efficacy of financial services firms in catering to women, both as customers and employees. Gravili et al (2019) examined GD across 28 European states and found a positive association between GD and FP. Zhang (2020) analyzed data from 2007 to 2014 and examined the impact of GD in the workforce.…”
Section: Gender Diversity (Gd) and Loan Size (Ls)mentioning
confidence: 99%